Seroprevalence of Antibodies to Avian Influenza A (H5) and A (H9) Viruses among Market Poultry Workers, Hanoi, Vietnam, 2001 - Uyeki, Timothy M. (Public Library of Science, 2012)
BACKGROUND: The frequency of avian influenza A virus infections among poultry workers is not well understood. METHODS: A seroprevalence study of market poultry workers and persons without occupational poultry exposure was conducted during 2001 in Hanoi, Vietnam. Sera were tested for avian influenza H5 and H9 antibodies by microneutralization and Western blot assays. RESULTS: Seroprevalence of H5 and H9 antibodies was 4% and 3% in poultry workers and 1% and 3.5% in non-poultry workers, respectively. CONCLUSIONS: Seroprevalence of H5 and H9 antibodies was low among Hanoi market poultry workers in 2001, but can serve as a baseline for additional studies.